Energy transduction ferroic materials. Issue 7 (September 2018) - Gao, Wenxiu; Brennan, Raymond; Hu, Yong; Wuttig, Manfred; Yuan, Guoliang; Quandt, Eckhard; Ren, Shenqiang
Graphical abstract: Ferroic materials and multiferroics, characterized by their ferroic orders, provide an efficient route for the coupling control of magnetic, mechanical, and electrical subsystems in energy transduction, which aims at converting one form of energy into another. A surge of interest in the ferroic coupling effect has stemmed from its potential use as a new versatile route for energy transduction. Here, the recent progress on the use of (multi)ferroic materials is reviewed, with special emphasis on the fundamental mechanisms that dictate the energy transduction process. Research on energy transduction ferroic materials paves the way for ubiquitous energy harvesting through magneto-mechano-electric-thermal coupling mechanisms. Finally, a summary and the future prospective directions of this field are discussed. Abstract: Ferroic materials and multiferroics, characterized by their ferroic orders, provide an efficient route for the coupling control of magnetic, mechanical, and electrical subsystems in energy transduction, which aims at converting one form of energy into another. A surge of interest in the ferroic coupling effect has stemmed from its potential use as a new versatile route for energy transduction. Here, the recent progress on the use of (multi)ferroic materials is reviewed, with special emphasis on the fundamental mechanisms that dictate the energy transduction process, including piezoelectricity, pyroelectricity, electrocaloric, magnetostriction, magnetocaloric, elastocaloric, magnetoelectricity, and emerging spin-charge conversion. Research on energy transduction ferroic materials paves the way for ubiquitous energy harvesting through magneto-mechano-electric-thermal coupling mechanisms. Finally, a summary and the future prospective directions of this field are discussed.